Stress–strain analysis of steel cylinders in walls surrounding Hong Kong–Zhuhai–Macau Bridge's artificial islands. (2nd January 2022) - Zhou, Binpeng; Li, Bin; Zhang, Fei; Liu, Siguo; Li, Yizheng
ABSTRACT: A vibration test was performed on large-diameter steel cylinders that comprise the wall surrounding the artificial islands of the Hong Kong–Zhuhai–Macau Bridge. The dynamic strain and stress endured by the following components, auxiliary cells of three different thicknesses, large and small mortises, and steel pipe piles, were analyzed. The results showed that the steel section at the monitored points of the auxiliary cell, mortise, and steel pipe pile did not yield during vibration. The extreme values of dynamic stress and strain of the auxiliary cell appeared near the bottom and increased with increasing auxiliary cell thickness. Meanwhile, the extreme values of dynamic stress and strain of mortises and steel pipe piles mostly appeared at the top. Our research results can provide a reference for the rationality of the auxiliary cell structure design and its safety evaluation.